Characteristics and the Side Effects of New MDR-TB Treatment in the Dr. Soetomo Hospital during 2016 - Umi Fatmawati; Tutik Kusmiati (Faculty of Medicine Universitas Airlangga, 2017)
Background: The Multi Drug Resistance Tuberculosis (MDR-TB) prevalence rate is by 6900 in which there are 1.9% of new cases and 12 % of cases fail. Indonesia ranks eighth out of 27 countries in the world. This study is aimed to investigate the characteristics of the new MDR TB patient demographic data, treatment, and side effects. Method: This research was analyzed retrospective data of the Medical Record (MR). Data were analyzed qualitatively. Results: The number of new patients are 82 people consisting of 41 men and 41 women. About 35 patients came from Surabaya and 47 were from outside Surabaya. Among those, 28 patients are 51–60 years old. Patients in the intensive phase (0–8 month) were 47 patient and 35 patients were in the continue phase 9–24 month. The main cause is the highest MDR-TB relapse 33 patients. Cycloserin and ethionamide prescribed to all of the subject followed by levofloxacin which is prescribed to 68 patients. The other medication were kanamycin, capreomycon, moxifloxacin and Para Amino Salicylat (PAS) which administered to 27,14,7 patient consecutively. Nausea is the one of the Adverse Drug reaction (ADR) that is preverly emerged. There were 30 patients complary this ADR and treatment which Omeprazole and Ranitidin. Conclusion: Characteristics of patients greatly differed between patients categories. In Soetomo hospital effort should be made to improve management case, drug and prevent or eliminate adverse drug reaction.